INTERTWINING FATE OF PROLACTIN AND METABOLISM: THE OVERLOOKED CAUSAL EFFECT RELATIONSHIP - MM, Nur Hidayah; R, Subashini (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Hyperprolactinaemia has always been regarded as an excess of hormones resulting in metabolic abnormalities. However, recent studies have shown that prolactin has a protective value against metabolic disorders in obese individuals.1 Increased circulating prolactin inhibits adipocyte hypertrophy, downregulates expression of inflammatory cytokines in visceral adipose tissue and alleviates insulin resistance.1 However, chronically high prolactin influences orexigenic-anorexigenic hormones, resulting in hyperphagia, weight gain and obesity.2 We present a patient with Metabolically-Healthy-Obesity [MHO] with hyperprolactinemia. CASE A 33-year-old male, presented with hypogonadism and infertility. His symptoms of hypogonadism preceded an increase in weight of 40 kg within two years. Blood pressure was 112/78 mmHg. He had sparse facial and axillary hair with Tanner stage 2. His latest weight was 164 kg (BMI 52 kg/m2 ). He had no acanthosis nigricans. His serum prolactin was 5985 m IU/L. He had low fasting morning serum testosterone [1.11 nmol/L]. FSH and LH levels were both low [0.3 IU/L]. His metabolic parameters were all normal: HDL 1.1, LDL 2.7, Triglyceride 1.1 (mmol/L), HbA1c 5.3%, Fasting Blood Sugar 4.7 mmol/L. MRI showed pituitary microadenoma. Other anterior pituitary hormonal assays were normal. He was started on Cabergoline 0.5 mg once a week. CONCLUSION The relationship between hyperprolactinemia and obesity is complex. In our patient, the sudden weight gain coincided with symptoms of hypogonadism due to hyperprolactinaemia. Thus, hyperprolactinaemia may have contributed to his weight gain. He also has normal metabolic parameters despite being obese class 3, which could indicate the protective value of elevated prolactin levels. In treating obese patients with hyperprolactinemia, a prolactin level that is too high or too low is proven to be unfavourable.3 Thus, treatment with cabergoline has been shown to help in reducing weight in this group of patients while keeping the serum prolactin at a slightly higher level to avoid diminishing the protective value of prolactin in obese patients.3,4,5